Pengaruh Kekuatan Sosial Dan Politik Dalam Pembentukan Peraturan Perundang-Undangan di Indonesia - Abdul Rahman Prakoso (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
The formation of laws and regulations in Indonesia is regulated in Law Number 12 of 2011 which was updated by Law Number 15 of 2019. One of the legal products made by the legislature is Law Number 3 of 2022 concerning the State Capital. The process of ratifying the Draft Law on the State Capital was only carried out 40 days after the DPR formed a Special Committee for the Draft IKN Law on December 7 2021. Community participation was not involved much in the drafting of this law. The political configuration in Indonesia is run democratically through people's representatives to express criticism of the government. Political influence underlies the speedy passage of Law Number 3 of 2022 concerning the State Capital. The majority of factions in the Indonesian House of Representatives approved and accepted with a note to ratify the IKN Law. Social considerations to pass the Law on the State Capital because the urgency of the Jakarta area is too heavy as the center of government, business center, trade center, financial center and service center.